1988
DOI: 10.1111/j.1439-0523.1988.tb00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Hybrid Necrosis in Rye

Abstract: In dipioid rj--e, two genes were detected which cause hybrid necrosis by compiementar}' action if both are present in dominant condition. Moreover, the,se genes cause hybrid necrosis in tnticale complementing with either one of the two genes, Nel and Nel, which are known to cause hybrid necrosis m wheat. It is suggested, that the two genes in rye are named Nerl and Ner2 corresponding to the wheat gene with which they complement in triticaie. The consequences of the presence of necrosis genes in rj-e popuiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Two genes for hybrid necrosis were found in inbred rye lines. They were complementary to each other and to corresponding genes for hybrid necrosis in wheat [9]. As early as in 1937, Dobzhansky suggested existence of comple-mentary genes, determining lethality or sterility in distant hybrids [10].…”
Section: Discussionmentioning
confidence: 99%
“…Two genes for hybrid necrosis were found in inbred rye lines. They were complementary to each other and to corresponding genes for hybrid necrosis in wheat [9]. As early as in 1937, Dobzhansky suggested existence of comple-mentary genes, determining lethality or sterility in distant hybrids [10].…”
Section: Discussionmentioning
confidence: 99%
“…These include the hybrid necrosis genes Ne1, Ne2 (Tsunewaki 1960, Hermsen 1963, two types of hybrid chlorosis (Ch1, Ch2; Hermsen 1966 and Cs1, Cs2;Kawahara 1993), and hybrid dwarfness (D1, D2, D3, D4;McMillan 1937, Hermsen 1967, Worland and Law 1980. The expression of chlorosis in certain wheat x rye hybrids led Tomar and Singh (1998) to propose the existence of the gene Clr1 in rye, while the two dominant complementary hybrid necrosis rye genes Ner1 and Ner2 are well established (Scoles 1985, Ren andLelley 1988). The dominant alleles of these two genes complement each other within the species, as well as in species hybrids.…”
Section: Discussionmentioning
confidence: 96%
“…Besides embryo lethality, hybrid dwarfness, hybrid weakness, necrosis/chlorosis, morphological abnormalities, and sterility are some of the consequences (e.g. Ren and Lelley 1988, 1989, Tomar and Singh 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid necrosis genes, including Ne1 and Ne2 in bread wheat, Net1 and Net2 in synthetic hexaploid wheat, and Ner1 and Ner2 in rye, have been mapped in cereal crops. Ne1 , Ne2 and Net2 are located on chromosome arms 5BL, 2BS and 2DS, respectively (Chu et al 2006 ; Mizuno et al 2011 ; Ren and Lelley 1988 ). Previous studies have shown that Ne1 is expressed mainly in tetraploid wheat (Tsunewaki 1992 ; Vikas et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%